CAN COLOUR-CODED WASTE BINS HELP IMPROVE WASTE MANAGEMENT IN LOKOJA, KOGI STATE, NIGERIA? - Olatunde-Aiyedun, Tope Gloria; Obaje, Mustapha; Otu, Halimat Sadiyat (Proceeding of International Conference on Social Science and Humanity, 2026)
Objective:  This study attempts to narrow the gap in the implementation of how people perceive, accept, and interpret challenges of color-coded waste bin systems in Nigerian cities, particularly in Lokoja, Kogi State, as a response to the challenges of municipal solid waste management. Method: This study employed a qualitative research design to investigate in-depth viewpoints, experiences, and recommendations regarding current waste management procedures and solutions. A total of twenty purposefully chosen participants were involved: ten residents (R1–R10), five local government representatives (LG1–LG5), three waste collectors (WC1–WC3), and two community leaders (CL1–CL2). Phenomenology was used to understand how different stakeholders perceive and experience issues related to waste segregation, focusing on the possibility of color-coded bins. Data were collected using semi-structured interviews and focus groups, then transcribed verbatim and analyzed thematically using NVivo 12. Results: The results indicated that the adoption of color-coded bins based on traffic signal colors that are already culturally familiar was viewed favorably, despite potential obstacles such as cost, low education levels, and enforcement challenges. Participants also highlighted the financial and environmental benefits, including increased recycling rates, reduced landfill reliance, and income streams. Overall, there was moderate awareness of waste management challenges, and the color-coded bins were seen as a culturally relevant and pragmatic solution to waste disposal issues in Lokoja. Novelty: This study presents a novel approach to addressing municipal waste management issues in Nigerian cities by introducing a color-coded bin system that is culturally familiar and practically applicable, aiming to improve waste segregation. The study also emphasizes the need for collaboration among government agencies, community stakeholders, academic institutions, and international partners to ensure the successful implementation of such interventions.